Well-Being dan Happiness Pengemis Jalanan di Surabaya - Putri Purnamasari; Ananta Yudiarso; Marselius Sampe Tondok (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2020)
Abstract - The phenomenon of street beggars to be one of the problems in Surabaya city. Life in the city, will bring psychological burden such as dissatisfaction, loss of life spirit, inner problems and problems to others, etc. Consequences received as street beggars can also elicit other psychological problems. This study is a descriptive study that aims to know the picture of well- being and happiness on street beggars in Surabaya. Sampling was done by snowball sampling and obtained the number of samples of 80 subjects. Data were taken using a questionnaire from the adaptation scale of Ryff's Scale of Psychological Well-Being (PWB) and the adaptation scale of Oxford Happiness Questionnaire (OHQ). The results showed that the well-being of street beggars tends to be high as much as 34%, 60% tends to be moderate and 6% tends to be low.. Street beggars have a high well-being because most of them are able to realize the purpose of life according to their standard of living. The joy of street beggars is known amongst them; quite happy (31%), feeling happier or happier (34%), and feeling unhappy (35%).Keywords: well-being, happiness, street beggars. Abstrak - Fenomena pengemis jalanan menjadi salah satu permasalahan di kota Surabaya. Kehidupan di kota memunculkan beban psikologis seperti ketidakpuasan, kehilangan semangat hidup, masalah batin dan masalah terhadap orang lain. Konsekuensi yang diterima sebagai pengemis jalanan juga dapat memunculkan permasalahan psikologis lainnya. Penelitian ini merupakan studi deskriptif yang bertujuan untuk mengetahui gambaran well-being dan happiness pada pengemis jalanan yang ada di Kota Surabaya. Pengambilan sampel penelitian dilakukan dengan snowball sampling dan diperoleh jumlah sampel sebanyak 80 subjek. Data diambil menggunakan kuesioner dari skala adaptasi dari Ryff’s Scale of Psychological Well-Being (PWB) dan skala adaptasi dari Oxford Happiness Questionnaire (OHQ). Hasil penelitian diketahui well-being yang dimiliki pengemis jalanan cenderung tinggi sebanyak 34%, cenderung sedang 60% dan cenderung rendah 6%. Pengemis jalanan memiliki well-being yang tinggi dikarenakan kebanyakan dari mereka mampu merealisasikan tujuan hidup sesuai dengan standar hidup mereka masing- masing. Kebahagiaan pengemis jalanan diketahui diantaranya; cukup bahagia (31%), merasa lebih bahagia atau bahagia (34%), serta merasa tidak bahagia (35%).Kata kunci: kesejahteraan, kebahagiaan, pengemis jalanan